The Surd in Theology - Magnusson, P. Magnus (The biblical world, 1919)
For the benefit of those whose memory of their mathematical experience may be somewhat weak, we would say that in mathematics a surd is defined as "an irrational number of quantity, especially an indicated root that cannot be extracted, as √2."